Perceived learning and satisfaction in a blended teacher education program: an experience of Malaysian teacher trainees - Karimi, Leila; Tunku Ahmad, Tunku Badariah (Anadolu University, Turkey, 2013)

(untitled)
Blended learning, as a new approach to education, is rapidly being adopted by educational institutions for the purpose of teacher education or teacher training. This study reports the results of a survey exploring the relationships between perceived learning and satisfaction in a blended teacher education program among three different groups of specialization at the Institute of Education, International Islamic University Malaysia (IIUM). This study was mainly exploratory in nature, employing specifically the quantitative research method, utilizing cross-sectional survey as the method of data collection. The respondents consisted of 170 teacher trainees who were randomly selected through quota sampling. The instrument used to collect data was a modified questionnaire that measured the respondents’ perception of learning and satisfaction in the blended teacher education program. The respondents reported high levels of perceived learning and satisfaction toward the blended teacher education program. The results showed positive and moderate correlation between perceived learning and satisfaction, while there was no statistically significant difference among all groups of teacher trainees’ perception of learning and satisfaction.